2019
DOI: 10.1111/jbi.13594
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and spatial variables are major determinants of fungal community in karst caves in Southwest China

Abstract: Aim Previous studies primarily based on the culture method have revealed that caves host a high fungal diversity and that exogenous carbon sources influence fungal communities. Here, we assess the fungal diversity and distribution patterns in karst caves in Southwest China and reveal the major factors that shape the fungal communities. Location Southwest China. Methods Samples of air, rock, sediment and water were collected from eight caves in Southwest China. Using high‐throughput sequencing of the internal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 82 publications
5
28
0
Order By: Relevance
“…These observations suggest a similar biogeography of DT and RT fungi in mangrove sediments, which is consistent with previous studies of bacterial communities in coastal Antarctic lakes [98] and microeukaryotic communities in Tingjiang River [53]. In agreement with these observations on the effect of geographic location on fungal community, Zhang et al [9] reported a similar distribution of archaea and bacteria in mangrove sediments in China, indicating that microbial communities in mangrove sediments are strongly shaped by the geographical location, possibly because of the combined effects of climate, niche conservatism, and rates of dispersal, evolutionary radiation and extinction [94,99]. Depth is a known and important factor that strongly affects microbial communities in mangrove sediments [8,16,27].…”
Section: Spatial and Environmental Selections On Fungal Communities Isupporting
confidence: 81%
“…These observations suggest a similar biogeography of DT and RT fungi in mangrove sediments, which is consistent with previous studies of bacterial communities in coastal Antarctic lakes [98] and microeukaryotic communities in Tingjiang River [53]. In agreement with these observations on the effect of geographic location on fungal community, Zhang et al [9] reported a similar distribution of archaea and bacteria in mangrove sediments in China, indicating that microbial communities in mangrove sediments are strongly shaped by the geographical location, possibly because of the combined effects of climate, niche conservatism, and rates of dispersal, evolutionary radiation and extinction [94,99]. Depth is a known and important factor that strongly affects microbial communities in mangrove sediments [8,16,27].…”
Section: Spatial and Environmental Selections On Fungal Communities Isupporting
confidence: 81%
“…The cave sampling strategy was described in our previous study (Zhang and Cai, 2019). In each cave, four to six sampling sites, interspersed at equal distances, were chosen along a transect.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, samples of air, water, rock, and sediment were intensively collected from eight karst caves in southwest China. The study of their mycobiomes indicated that both sample types and spatial variables were the key determinants of fungal distributions (Zhang and Cai, 2019). In this report, we focus on the features of and factors shaping the bacterial community in those same eight caves.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these observations, Zhang et al ( 13 ) reported a similar geographical distribution of the prokaryotic community in mangrove sediments, indicating a crucial role of geographical location in shaping archaeal communities in mangrove sediments. The pronounced effects of geographical location are possibly associated with the combined effects of climate, niche conservatism, and rates of dispersal, evolutionary radiation, and extinction in different environments ( 34 , 57 ). Although the always-rare taxon community did not cluster as well as the all-taxon, dominant taxon, and conditionally rare taxon communities, PERMANOVA supported significant differences between always-rare taxon communities among mangroves ( Fig.…”
Section: Discussionmentioning
confidence: 99%